Therapeutic Effect of Virechana (Therapeutic purgation) on Insulin Resistance among Prediabetic Individuals: A Case Series - Dr. Shailesh V Deshpande; Dr. Anany Trivedi; Dr. Vaishali S Deshpande; Dr. Divya B (The Bioscan, 2025)
Background: Prediabetes is a state of impaired glucose regulation strongly linked with insulin resistance, obesity, and metabolic dysfunction. It carries a high risk of progression to type 2 diabetes mellitus (T2DM) and associated cardiovascular and microvascular complications. Conventional management relies on lifestyle modification, but adherence is often challenging. Ayurveda describes Prameha as a Bahudoshaja Vyadhi, in which Shodhana therapies are recommended in the early stages. Among these, Virechana Karma (therapeutic purgation) is considered the prime intervention for Kapha–Pitta predominant conditions. Objective: To evaluate the effect of Virechana Karma on insulin resistance, glycaemic indices, and lipid parameters in individuals with prediabetes. Methodology: This case series included three prediabetic patients aged 39–52 years who met the American Diabetes Association (ADA) criteria and were clinically fit for Virechana. The intervention involved a standard protocol comprising Deepana-Pachana, Snehapana, Abhyanga, Swedana, and administration of Trivrut Lehyam for purgation, followed by Samsarjana Krama. Key assessment parameters included fasting serum insulin, HOMA-IR, fasting and postprandial blood sugar, and lipid profile, measured before and after therapy. Results: All participants achieved Madhyama Shuddhi and demonstrated improvements in metabolic parameters. Fasting serum insulin and HOMA-IR values decreased, indicating enhanced insulin sensitivity. Both fasting and postprandial blood sugar levels declined, reflecting better glycemic control. Lipid parameters showed favorable modulation, with reductions in total cholesterol, triglycerides, LDL, and VLDL levels. HDL changes varied, though overall cholesterol/HDL and LDL/HDL ratios improved, suggesting a healthier cardiometabolic profile. Conclusion: Virechana Karma produced a notable reduction in insulin resistance and improved glycemic and lipid parameters among prediabetic individuals. These findings support its potential role as an early Ayurvedic intervention to restore metabolic balance and delay progression to T2DM. Larger clinical studies are warranted to validate these preliminary observations.